La enseñanza musical en el Colegio Nacional de Sordomudos y Ciegos de España desde su fundación hasta la primera república: una aproximación documental - Burgos Bordonau, Esther (Revista General de Información y Documentación, 2004)
A documental study of the National School for the Deaf-Mute and Blind in Madrid as an example of an institution that, in addition to primary education and the teaching of trades, also offered musical education to its blind pupils.